4G network capacity expansion system based on service perception - Limin TANG; Deping XU; Ritao CHENG (Dianxin kexue)
In the view of the limitations of current 4G network capacity expansion standards,the perception and evaluation standard of classification of service was formulated from the service perception,and the correlation between the service perception and network was studied,which loaded to determine the threshold of capacity expansion in various types of services.